Nepal Development Update : Global Challenges and Domestic Revival - World Bank (Washington, DC, 2022)
Nepal continues to struggle with the COVID-19 pandemic, but the ongoing COVID-19 vaccination drive has helped to reduce the fatality rate. The country experienced a first wave in March 2020, a second wave in mid-April 2021, and a third wave in January 2022. In response, social distancing measures were imposed but gradually became less stringent as COVID-19 progressed from the first to the third wave, driven in part by the COVID-19 vaccination drive that began in January 2021. Vaccination also contributed to a reduction in the fatality rate. As of March 2022, more than 60 percent of the population has received two doses of COVID-19 vaccines. High frequency indicators suggest that the economy continued to recover in the first half of FY22 after rebounding in FY21 from a contraction in FY20.